A new species of Secutor (Teleostei: Leiognathidae) from the Western Indian Ocean - Baldwin, Zachary H.; Sparks, John S. (Zootaxa, 2011)
A new species of ponyfish, Secutor mazavasaoka, is described from coastal waters of the Western Indian Ocean. Together, the new species, S. indicius, and S. insidiator are readily distinguished from congeners by more or less oval-shaped elongate bodies (vs. markedly deep and disk-shaped). The new species is distinguished from S. hanedai by the presence of scales on the chest (vs. chest asquamate), and from S. indicius and S. insidiator by a deeper, hatchet-shaped body (vs. uniformly oval) and pigmentation pattern on the dorsal flank comprising eight to eleven well-defined columns of irregular small spots and blotches (vs. 14 to 17 thin columns of spots or vertical lines in S. indicius, or larger irregular blotches arrayed in poorly defined columns in S. insidiator). Additionally, the new species is distinguished from S. insidiator by a strongly upturned mouth and compressed pug-like snout, a pronounced concavity dorsal to the orbit, a dorsally-projecting nuchal spine, and dorsal-fin insertion well posterior to vertical through pectoral-fin base (vs. at about level of pectoral-fin base in S. insidiator).